Art Re-Call: Riverscapes IN FLUX redefines art as life - Garcia, Elenita de la Rosa (Silliman Journal, 2022)
The exhibit Riverscapes: IN FLUX, a joint project of the Goethe Institute Philippines and the Metropolitan Museum of Manila, which opened on 14 March 2013 features the works of Southeast Asian artists focused on the changing riverscapes in the region. The Art Talk that followed on 16 March 2013 affirms the artists’ general intention to document the changes in the environment brought about by technological advancements and globalization. The installations, addressing not only the sense of sight but of touch and smell among others, and expressly addressing socio-political issues are another set of artworks that defy the traditional idea of art, especially those exhibited in a museum. This paper explores the possibility that Riverscapes: IN FLUX embodies alternative aesthetics that Western philosophers like Nietzsche and Heidegger were looking for, as well as the Japanese aesthetics of Wabi-Sabi.